Farmers’ use of improved agricultural inputs and practices: review and synthesis of research in Ethiopia - Ayele, Seife; Bosire, Caroline K. (International Livestock Research Institute, 2011)
Ethiopia’s agriculture is typically subsistence, low input‐low output, and rainfed. In the light of a renewed government strategy to use improved inputs and practices to enhance smallholder agricultural productivity and production, strengthening the evidence‐base for the design and implementation of such a strategy becomes central. This paper reviews and synthesizes the findings of seven recent graduate theses researched in Ethiopia, and aims to identify underlying factors influencing the use of improved agricultural inputs among farmers. It shows that farmers’ education strongly influences improved input use across activity areas. Smallholder farmers who used such inputs for commercial production of crops and livestock products are better able to assess market opportunities, have more assets and/or income, and have better access to extension services and credit. However a large number of factors that influence improved inputs use were technology or location specific. The evidence suggests that transforming subsistence, low input‐low output agriculture into market‐oriented, high inputhigh output agriculture entails diverse strategies including promoting cross‐cutting factors like education, infrastructure and participation from women in agricultural development, and equally, targeting interventions like credit to the specific needs of farmers, their local contexts and technological attributes.